Drug stereochemistry analytical methods and pharmacology - Jozwiak, Krzysztof, 1971-; Lough, W. J. (W. John); Wainer, Irving W. (Drugs and the pharmaceutical sciences ;, 2012)
Updated to reflect modern advances in the techniques and methodology of drug stereochemistry, the Third Edition comprehensively presents all aspects of chiral drugs from scientific, academic, governmental, industrial, and clinical points of view. This stand-alone text covers the lifespan of stereochemistry, from its early history, including an overview of terms and concepts, to the current drug development process, legal and regulatory issues, and the new stereoisomeric drugs. New topics in the Third Edition include: The use of enzymes in the synthesis and resolution of enantiometrically pure compounds in drug discovery; How stereochemistry impacts decisions made in the Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) stages of drug discovery; A chapter on pharmacokinetics and pharmacodynamics that discusses the issues faced during the final stages of the drug development process; The impact of International Conference on Harmonisation on the use of single isomer drugs; Racemic switches; The concept of molecular chiral recognition and how it affects the separation and behavior of stereochemically pure drugs; A chapter on the legal perspectives of patent issues surrounding racemic switches and the marketing of single enantiomer switches.